CULTURAL APPROACH THROUGH TRADITIONAL DANCE IN INDONESIAN LANGUAGE LEARNING FOR FOREIGN SPEAKERS: PEDAGOGICAL INNOVATION IN THE GLOBAL BIPA PROGRAM: CULTURAL APPROACH THROUGH TRADITIONAL DANCE IN INDONESIAN LANGUAGE LEARNING FOR FOREIGN SPEAKERS: PEDAGOGICAL INNOVATION IN THE GLOBAL BIPA PROGRAM - Nuraida, Ida; Nursilah, Nursilah; Ayodele, Osiyemi Olusegun (International Journal of Performing Arts (IJPA), 2025)
This study aims to explore the effectiveness of cultural approaches through the integration oftraditional dance in the teaching of Indonesian as a Foreign Language (BIPA) at Hebei ForeignStudies University (HISU), China. The primary focus is on the use of Jathilan (a traditional Javanesedance) and Betawi dance as instructional media to foster cultural awareness and enhance languageskills among international learners. This qualitative case study involved data collection throughdirect observation of both online and offline learning sessions, as well as in-depth interviews withBIPA instructors and participants actively involved in the dance-based learning process. Thefindings indicate that the incorporation of traditional dance significantly boosts learners’motivation, deepens their understanding of Indonesian culture, and creates an inclusive andparticipatory classroom environment. Active involvement in dance practice also strengthensstudents’ emotional and cognitive engagement in language learning. A key element in the success ofthis program is the collaboration between Universitas Negeri Jakarta (UNJ) and HISU through aninternational community service initiative. The study concludes that performing arts-based culturalapproaches offer an innovative pedagogical strategy for BIPA instruction and serve as an effectivetool for Indonesia’s cultural diplomacy on the global stage.